Undiagnosed diabetes based on HbA 1c by socioeconomic status and healthcare consumption in the Tromsø Study 1994-2016 - Lopez-Doriga Ruiz, Paz; Hopstock, Laila Arnesdatter; Eggen, Anne Elise; Njølstad, Inger; Grimnes, Guri; Stene, Lars Christian Mørch; Gulseth, Hanne Løvdal (BMJ Open Diabetes Research & Care, 2021)
Introduction - We aimed to investigate whether the proportion of undiagnosed diabetes varies by socioeconomic status and healthcare consumption, in a Norwegian population screened with glycated hemoglobin (HbA1c). Research - design and methods In this cohort study, we studied age-standardized diabetes prevalence using data from men and women aged 40–89 years participating in four surveys of the Tromsø Study with available data on HbA1c and self-reported diabetes: 1994–1995 (n=6720), 2001 (n=5831), 2007–2008 (n=11 987), and 2015–2016 (n=20 170). We defined undiagnosed diabetes as HbA1c ≥6.5% (48 mmol/mol) and no self-reported diabetes. We studied the association of education, income and contact with a general practitioner on undiagnosed diabetes and estimated adjusted prevalence ratio (aPR) from multivariable adjusted (age, sex, body mass index) log-binomial regression. Results - Higher education was associated with lower prevalence of diagnosed and undiagnosed diabetes. Those with secondary and tertiary education had lower prevalence of undiagnosed diabetes (aPR for tertiary vs primary: 0.54, 95% CI: 0.44 to 0.66). Undiagnosed as a proportion of all diabetes was also significantly lower in those with tertiary education (aPR:0.78, 95% CI: 0.65 to 0.93). Household income was also negatively associated with prevalence of undiagnosed diabetes. Across the surveys, approximately 80% of those with undiagnosed diabetes had been in contact with a general practitioner the last year, similar to those without diabetes. Conclusions - Undiagnosed diabetes was lower among participants with higher education. The hypothesis that those with undiagnosed diabetes had been less in contact with a general practitioner was not supported.